(OC-6-13)-bis(acetone) dihydrido-bis(tricyclohexylphosphine)iridium(III) tetrafluoridoborate acetone solvate - Heinemann, Frank Wilhelm; et al. (Acta Crystallographica Section E: Structure Reports Online, 2007)
The title solvated salt, [Ir(H)(2)P(C6H11)(3)(2)OC(CH3)(2)(2)]BF4 center dot-( CH3)(2)CO, was obtained by the protonation of [ Ir(H)(5)- P(C6H11)(3)(2)] with HBF4 in acetone. The cation features OC-6- 13 stereochemistry, with Ir - P = 2.3159 ( 6) and 2.3267 ( 6) angstrom, and Ir - O = 2.238 ( 1) and 2.276 ( 1) angstrom. The BF4- anion shows threefold rotational disorder about a B - F bond, with site occupancies of 0.65, 0.25 and 0.10. While there are several intramolecular C-H center dot center dot center dot O and intermolecular C-H center dot center dot center dot F hydrogen-bonding interactions [ C center dot center dot center dot O = 3.207 ( 3)-3.358 ( 3)angstrom, and C center dot center dot center dot F = 3.434 ( 3) and 3.441 ( 3) angstrom], the O atom of the acetone solvent molecule does not act as a C - H acceptor.